Development and Validation of a TaqMan Real-Time PCR Assay for the Specific Detection and Quantification of Fusarium fujikuroi in Rice Plants and Seeds - Carneiro, Greice Amaral; Matić, Slavica; Ortu, Giuseppe; Garibaldi, Angelo; Spadaro, Davide; Gullino, Maria Lodovica (Phytopathology, 2017)
Bakanae disease, which is caused by the seedborne pathogen Fusarium fujikuroi, is found throughout the world on rice. A TaqMan real-time PCR has been developed on the TEF 1-α gene to detect F. fujikuroi in different rice tissues. Three primer/probe sets were tested. The selected set produced an amplicon of 84 bp and was specific for F. fujikuroi with respect to eight Fusarium species of rice and six other rice common pathogens. The assay was validated for specificity, selectivity, sensitivity, repeatability, and reproducibility. The detection limit was set at 27.5 fg of DNA, which is approximately equivalent to one haploid genome of F. fujikuroi. The developed TaqMan real-time assay was able to efficiently detect and quantify F. fujikuroi from rice culms, leaves, roots, and seeds. At 1 week post-germination (wpg), the pathogen was more diffused in the green tissues, while at 3 wpg it was uniformly spread also in the roots. The highest concentration of F. fujikuroi was measured in the M6 cultivar, which showed around 1,450 fungal cells/g. The assay was sufficiently sensitive to detect a few genomic equivalents in the rice seeds, corresponding to 9.89 F. fujikuroi cells/g. The assay permitted bakanae disease to be detected in asymptomatic tissues at the early rice development stages.